Improving seed germination, growth, and biochemical characteristics of corn seedling via the application of silver nanoparticles synthesized from fennel (Foeniculum vulgare) - Mehdi Afrouz; Parisa Sheikhzadeh (علوم و فناوری بذر ایران)
In order to evaluate the effect of Ag synthesized from fennel on seed germination, growth and biochemical characteristics of hybrid single cross 704 corn seedlings, an experiment was carried out in a randomized complete block design with three replications at the University of Mohaghegh Ardabili in 2021. Experimental factors included synthesized Ag nanoparticles (0, 0.001, 0.1, 0.25, and 0.75 mg L-1) and the application methods of Ag nanoparticles (seed priming and no priming). The results showed that in both methods of nanoparticle application, with the use of different concentrations of Ag nanoparticles, there was a significant increase in the percentage and speed of germination, average daily germination, germination simultaneity index, strength index, length and dry weight of corn seedlings and a decrease in the average germination time, D50 of corn seeds were germinated. Among the nanoparticle application methods, priming seeds with 0.001 mg L-1 and adding 0.1 mg L-1 Ag nanoparticles had a greater effect on improving germination, seedling growth, and increasing seed vigor index. By adding 0.1 mg L-1 of Ag nanoparticles to no priming, it resulted in the highest germination%, synchronicity index, mean daily germination and the lowest mean germination time. The use of different concentrations of Ag nanoparticles in both application methods increased the activity of catalase, peroxidase, polyphenol oxidase and proline content compared to the control treatment, the use of a concentration of 0.001 mg L-1 of Ag nanoparticles as a priming can be suggested to improve seed germination, growth, and biochemical characteristics of corn seedlings.